Alat Pengatur Pakan Ayam Petelur Berbasis IoT Menggunakan Microkontroller ESP8266 - Ade Oktora; Iim Abdurohim (Journal Data Science, Technology, Informatics and Security, 2023)
Modern agriculture is increasingly adopting information and communication technology to enhance efficiency and productivity. In this context, this research presents an innovative device in the form of an automatic feeder for laying hens, utilizing Internet of Things (IoT) technology and the ESP8266 microcontroller. This device is designed to automate the feeding process of laying hens, ensuring they receive the right nutrition at the right times. The ESP8266 microcontroller serves as the brain of this device, connecting to Wi-Fi networks and allowing remote access via a mobile application or web-based platform. The device is equipped with sensors to monitor the remaining feed levels and provide information about the environmental conditions within the chicken coop. Furthermore, intelligent algorithms are applied to optimize the feeding schedule based on the collected data. Experimental results demonstrate that this device can enhance feed efficiency, reduce waste, and significantly improve the well-being of laying hens. Additionally, real-time monitoring via a mobile application enables farmers to take prompt action in case of issues within the coop. This research underscores the significant potential of IoT applications in agriculture, particularly in livestock management. The automated feeder not only offers economic benefits but also supports sustainable farming practices through more efficient resource utilization.